Pengaruh Preventive Maintenance Terhadap Performa Unit Excavator Komatsu PC 200-8 di PT PP Presisi Jobsite Main Hauling Road PT Hengjaya Mineralindo - Prihadianto, Braam Delfian; Wiyono, Al Difa Naufal Akmal; Winarto, Felixtianus Eko Wismo; Harjono (Jurnal Teknik Mesin Indonesia, 2025)
Excavators are multi-purpose equipment that has various functions. To keep the excavator in top condition even though it’s used continuously, it’s necessary to carry out preventive maintenance on the excavator unit. Preventive maintenance is maintenance carried out on a unit to prevent unexpected damage and to find conditions that could cause damage when using the unit. The reality in the field is that there are many delays in implementing preventive maintenance on excavator. Delays that occur will have an impact on the excavator both in terms of unit condition and unit productivity. This study aims to analyze the effect of preventive maintenance on excavator units in the period February to June 2023 using the Physical Availability, Mechanical Availability, and Effective Utility calculation methods, as the potential lost costs that the company will incur if there is a delay in preventive maintenance on the excavator unit. The analysis results show that units with timely preventive maintenance have a higher average value of 28% for PA, 31.7% for MA, and 24.8% for EU. Delays in preventive maintenance affect the condition of the unit, where the lifetime of a component should be used longer. The estimated losses experienced by the company were estimated at IDR 433,700,000 per unit during the data collection period, from the total units that experienced delays in preventive maintenance.